Liszt's Representation of Instrumental Sounds on the Piano : Colors in Black and White - Kim, Hyun Joo, 1978- (Book collections on Project MUSE., 2019)
Examines Liszt's piano arrangements of music originally created for other instruments, especially the symphony orchestra and the Hungarian Gypsy band.